Opportunity, identity, and resources in ethnic mobilization : the Iraqi Kurds and the Abkhaz of Georgia - Fawaz, Ahmed Abdel-Hafez, 1976- (Lexington Books, 2017)
This book examines case studies of the Kurds in Iraq and the Abkhaz in Georgia to explore how ethnic identities become politicized by states and political entrepreneurs, leading to mobilization of ethnic populations. Through analysis of these cases, it provides a new theoretical framework to examine the process of ethnic mobilization.